2011
DOI: 10.1080/10406638.2011.572576
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PAH Metabolites in Bile of Common Carp,Cyprinus carpioL. with Fixed Wavelength Fluorescence in a Field and Laboratory Study

Abstract: The seasonal and inter-gender variability of polycyclic aromatic hydrocarbon (PAH) metabolites in the bile of common carp (Cyprinus carpio) was investigated with a field study in Karakaya Dam Lake (KDL) and a laboratory-conducted study with the fish samples of KDL and Sultansuyu Dam Lake (Turkey). The KDL has been polluted by urban, industrial, and agricultural activities for many years. A seasonal trend was seen in PAH metabolite levels with higher levels detected in May 2005 samples in KDL. Their levels in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…Multiple studies have shown that, in fish, bile fluorescence is directly proportional to the concentration of PAH metabolites, indicating that bile analysis is a sensitive method to quantify the amount of PAHs that are bioavailable . The optimal excitation/emission wavelength pair for both the parent compound and metabolites of fluoranthene was found to be 280 nm to 440 nm, similar to wavelength pairs stated in the literature .…”
Section: Resultssupporting
confidence: 73%
“…Multiple studies have shown that, in fish, bile fluorescence is directly proportional to the concentration of PAH metabolites, indicating that bile analysis is a sensitive method to quantify the amount of PAHs that are bioavailable . The optimal excitation/emission wavelength pair for both the parent compound and metabolites of fluoranthene was found to be 280 nm to 440 nm, similar to wavelength pairs stated in the literature .…”
Section: Resultssupporting
confidence: 73%